2018
DOI: 10.1186/s40246-018-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

APPLaUD: access for patients and participants to individual level uninterpreted genomic data

Abstract: BackgroundThere is a growing support for the stance that patients and research participants should have better and easier access to their raw (uninterpreted) genomic sequence data in both clinical and research contexts.Main bodyWe review legal frameworks and literature on the benefits, risks, and practical barriers of providing individuals access to their data. We also survey genomic sequencing initiatives that provide or plan to provide individual access. Many patients and research participants expect to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 21 publications
0
59
0
Order By: Relevance
“…The results show a relatively high willingness among participants to share information with their social circle but an overall strong reluctance to share data with official institutions (employers, health insurance) due to fear of genetic discrimination. Several studies showed that, while there are limits in regard to people's willingness to share genetic information, there is a significant interest in sharing it for research purposes (e.g., in health data cooperatives) medical progress (Wicks et al, 2010;Haga and O'Daniel, 2011;Hafen et al, 2014;Aitken et al, 2016;Thorogood et al, 2018). This can be interpreted as openness to the shared exchange of genetic information when societal benefits are expected.…”
Section: Discussionmentioning
confidence: 99%
“…The results show a relatively high willingness among participants to share information with their social circle but an overall strong reluctance to share data with official institutions (employers, health insurance) due to fear of genetic discrimination. Several studies showed that, while there are limits in regard to people's willingness to share genetic information, there is a significant interest in sharing it for research purposes (e.g., in health data cooperatives) medical progress (Wicks et al, 2010;Haga and O'Daniel, 2011;Hafen et al, 2014;Aitken et al, 2016;Thorogood et al, 2018). This can be interpreted as openness to the shared exchange of genetic information when societal benefits are expected.…”
Section: Discussionmentioning
confidence: 99%
“…How to safeguard participants' right to move their data around -by giving them their data in a machine-readable format, rather than as a printed PDF, for example -should be clarified. The code could also lay out what steps are necessary for responsible communication of health data to a patient or volunteer 12,13 . Should people who are being informed about the identification of genomic variants of malignant or unknown significance be offered genetic counselling, for instance?…”
Section: Code Of Conductmentioning
confidence: 99%
“…Thus, providing unconditional access to that kind of information may violate professional standards of care. Compounding matters are the European ethical standards mandating that genetic test results may not be provided to patients without proper genetic counselling [11,12]. This opens up the additional question of whether the GDPR access right could trump statutory and professional limitations on providing certain types of data to patients?…”
Section: A Case Against Myriad or Against The Doctor?mentioning
confidence: 99%